Evaluating Vocabulary, Mechanics, and Organization in High School Students' Descriptive Writing - hasna hunowu (PT MEDIA JURNAL DAN PENDIDIKAN, 2025)
Writing descriptive text requires a complex integration of vocabulary, mechanics, and organization, which often presents significant challenges for English as a Foreign Language (EFL) students. This study aims to describe and evaluate the writing abilities of second-grade students in composing descriptive texts, specifically focusing on their proficiency in vocabulary usage, mechanical accuracy, and paragraph organization at SMA Negeri 1 Popayato. Employing a qualitative descriptive design, the research gathered data through targeted writing tests administered to a random sample of 20 students. The data were analyzed and categorized using standardized scoring criteria. The synthesized results revealed that the students' overall writing ability falls into the average category, with a mean score of 45.4. Specifically, the highest frequency of errors occurred in vocabulary (55%), characterized by limited word range and direct native-language translation, followed by organizational flaws (50%) and mechanical errors in capitalization and punctuation (45%). In conclusion, the students require targeted instructional strategies emphasizing contextual vocabulary building and mechanical practices to improve the coherence and accuracy of their descriptive writing